Contribution of Potato Farming Income to Household Income in Sungai Asam Village, Kayu Aro Barat District, Kerinci Regency - Sumarno, Wawan; Gusriati, Gusriati; Yanda, Febri (Baselang, 2023)
The study aims to analyze the contribution of income from potato farming to total household income in Sungai Asam Village, Kayu Aro Barat District, Kerinci Regency. This study will be conducted from May to June 2023. The method of conducting research is the survey method. The number of sampling population in this study using the census method was 68 respondents. Data analysis using quantitative descriptive analysis). The contribution of income from potato farming to household income is 53.13% of the total income of potato farmers and is included in the medium category.